STRATEGI MANAJEMEN BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SMK NU KOTA TASIKMALAYA - Lusiana; Nugraha, Doni; Amarullah Malik (Program Studi Manajemen Pendidikan Islam, 2024)
Discipline in the learning process is an important thing and is the focus of attention for schools in an effort to improve it, therefore the school must be able to raise awareness for students to be able to behave disciplined well. The purpose of this study is to determine the guidance and counseling management strategy at SMK NU Tasikmalaya City, in an effort to improve student discipline at school. This study uses a qualitative descriptive approach, data sources obtained through observation, interviews, and documentation. The results of this study are 1) The guidance and counseling management strategy carried out at SMK NU Tasikmalaya City is to plan the annual work program, organize the process of grouping all tasks, responsibilities and authorities, supervise the implementation of guidance and counseling services, and evaluate each performance of guidance and counseling services, 2) Improving student discipline at SMK NU Tasikmalaya City, namely teachers enforce rules both in and outside the classroom, punish students who commit violations based on the violation points listed, 3) The guidance and counseling management strategy in improving student discipline carried out at SMK NU Tasikmalaya City includes providing basic services, responsive services, individual planning services, and individual planning service strategies, and 4) the obstacles faced by schools in improving student discipline are in the level of dress discipline, school policies, student attendance and home visits.